Optimization of gyrotron resonator’s dimensions - Kacper Nowak, Kacper; Dumbrajs, Olgerts (National Institute of Telecommunications, 2021)
This paper explains the procedure of determining the initial dimensions of a gyrotron resonator. In particular, the paper discusses which geometrical parameters impact the wave properties of the resonator. The solution is implemented using Matlab software and estimations are performed with the use of the SMath Studio spreadsheet. © 2021 National Institute of Telecommunications. All rights reserved.
Keywords: Research Subject Categories::NATURAL SCIENCES; Cold cavity; gyrotron design; Matlab code